Macular Retinal Ganglion Cell Complex Thickness and Its Relationship to the Optic Nerve Head Topography in Glaucomatous Eyes with Hemifield Defects. (1st November 2010) - Takagi, Seiji T.; Kita, Yoshiyuki; Takeyama, Asuka; Tomita, Goji
Abstract : Purpose . To evaluate the relationship between the macular ganglion cell complex (mGCC) thickness, which is the sum of the retinal nerve fiber, ganglion cell, and inner plexiform layers, measured with a spectral-domain optical coherence tomograph and the optic nerve head topography measured with a confocal scanning laser ophthalmoscope in glaucomatous eyes with visual field defects localized predominantly to either hemifield. Materials and Methods . The correlation between the mGCC thickness in hemispheres corresponding to hemifields with and without defects (damaged and intact hemispheres, respectively) and the optic nerve head topography corresponding to the respective hemispheres was evaluated in 18 glaucomatous eyes. Results . The mGCC thickness was significantly correlated with the rim volume, mean retinal nerve fiber layer thickness, and cross-sectional area of the retinal nerve fiber layer in both the intact and the damaged hemispheres ( P < .05 ) . Discussion . For detecting very early glaucomatous damage of the optic nerve, changes in the thicknesses of the inner retina in the macular area and peripapillary RNFL as well as rim volume changes in the optic nerve head are target parameters that should be carefully monitored.